When *y* is a function of *x*, then one value of *y* associated with one value of *x* from the domain of the function. This relationship is denoted by *y* = *f* (*x*), which is read as " *y* is equal to *f* of *x* " and it means that *y* is a function of *x*. Such a formula is called the functional notation.

For example, if *y* = 5 *x* + 11 then we can write this function as the notation *f* (*x*) = 5 *x* + 11.

Functional notation is used to find the value of *y* or *f* (*x*) associated with a certain value of *x*. If the function *y* = *f* (*x*) = 2 *x* – 5 is given, then for the values of *x* = 2, 5, or 8 we can find the corresponding values of *y* or *f* (*x*) by replacing them in the functional notation.